CENTENARIANS' END-OF-LIFE THOUGHTS AND PLANS: IS THEIR SOCIAL NETWORK ON THE SAME PAGE?. (11th November 2018) - Kim, K; Boerner, K; Kim, Y; Rott, C; Jopp, D S
Abstract: Centenarians are per definition very close to the end of their lives. Yet, little is known about their end-of-life (EOL) thoughts and plans, and even less is known about to what extent their primary contacts are aware of these thoughts. Using 78 dyads of centenarians and their proxies from the Second Heidelberg Centenarian Study, we examined dyadic correspondence on centenarians' EOL thoughts and planning. In nearly half of dyads, proxies misjudged whether the centenarian thought about the EOL. Only few centenarians perceived the EOL as threatening, but proxies overestimated; about a quarter of centenarians reported longing for death, but proxies underestimated. Proxies also reported more centenarians' EOL planning than centenarians themselves. Overall, many enrolled proxies did not know about centenarians' EOL thoughts and plans even though they were the persons very close to the centenarians, suggesting a lack of communication between centenarians and key social network members in this respect.